The Effects of Progressive Levels of Interactivity and Vividness in Web Marketing Sites - Thorson, Esther and (Journal of Advertising, 2001)
This experiment examines interactivity and vividness in commercial web sites. We expected increased levels of interactivity and vividness would lead to more positive attitudes toward web sites, stronger feelings of telepresence, and greater attitude--behavior consistency. In addition, we expected increased levels of vividness to lead to the development of more enduring attitudes toward the site. Participants explored four web sites. Increases in interactivity and vividness were associated with increased feelings of telepresence. In addition, increases in vividness were associated with more positive and more enduring attitudes toward the web site. Implications for new media researchers and practitioners are discussed.
https://katalog.adlr.link/Record/ai-55-aHR0cHM6Ly93d3cuanN0b3Iub3JnL3N0YWJsZS80MTg5MTg5